Language and financial decision making : survey experiment on Singapore savings bond - Ang, Shaoquan (2016)
We investigate the effect of language on economic decision making, with the focus on the allocation of endowment to financial products. To test this effect, we manipulated the original Singapore Savings Bond (SSB) fact sheet in three ways: (i) the use of stronger adjectives and adverbs, in particular stronger adjectives and adverbs; (ii) the use of future-tense; (ii) the use of both strong adjectives and adverbs, and future tense. Subjects are randomly allocated to each of the four treatments, and are required to make a decision on the amount to allocate to the SSB and five other alternative financial instruments. We found that the use of excessive strong adjectives and adverbs have a negative effect on people’s allocation to the SSB. Future-tense was found to have statistically insignificant positive effect. A secondary finding indicates that one with higher risk aversion will allocate more endowment to the virtually risk-free SSB. Explanations on these findings will be discussed further in this paper.